Titanogryllus n. gen., the largest Gryllinae cricket from the Neotropical Region with three new species from the Brazilian Atlantic Forest (Orthoptera, Grylloidea, Gryllidae) - Jaiswara, Ranjana; Souza-Dias, Pedro G. B.; de Campos, Lucas Denadai; Redü, Darlan R.; de Mello, Francisco De A. G.; Desutter-Grandcolas, Laure (Zootaxa, 2018)
Titanogryllus, a new genus and three new species T. salgado n. gen. n. sp., T. oxossi n. gen. n. sp., and T. oxente n. gen. n. sp. from subfamily Gryllinae (Grylloidea, Gryllidae) are described from the Brazilian Atlantic Forest. This genus is characterized by its very large size, and establishes a new record for the largest known cricket from Neotropical Region. The new taxa are characterized by their external morphology and male and female genitalia.